Effectiveness Evaluation of a Workshop Program to Enhance Learners’ Brain Skills and Develop the Brain through Positive Discipline of Executive Function (EF) at Ban Plong Municipal Kindergarten School: Application of Kirkpatrick’s Four-Level Evaluation : - - Nomanee, Jatupol; Unkong, Thidawan (Mahachula Academic Journal, 2025)
This research evaluated the effectiveness of a workshop designed to enhance learners’ brain skills and develop executive function (EF) through positive discipline at Ban Plong Municipality Kindergarten. The evaluation applied Kirkpatrick’s Four-Level Training Evaluation Model with the objectives to assess: 1) Reaction, 2) Learning, 3) Behavior, and 4) Results. The participants included 5 early childhood teachers and 84 parents, totaling 89 individuals. Data collection instruments comprised four questionnaires and evaluation forms based on the four levels: reaction, learning, behavior, and results assessments. Data analysis employed descriptive statistics (mean and standard deviation) and paired t-tests. The results indicated that: 1) participants’ overall satisfaction level was very high (Mean = 3.90, SD = 0.30); 2) the post-training learning scores (Mean = 33.7, SD = 5.4) were significantly higher than pre-training scores at the .001 level (t = -5.76, p < .001); 3) behavioral assessments showed statistically significant improvements in all measured behaviors post-training (p < 0.05); and 4) outcome evaluations demonstrated high skill levels across all participant groups, with mean scores of 3.4 or above.